The Globalization of Addiction: A Study in Poverty of the Spirit - Alexander, Bruce (Oxford University Press, 2010)
'The Globalization of Addiction' presents a radical rethink about the nature of addiction. Scientific medicine has failed when it comes to addiction. There are no reliable methods to cure it, prevent it, or take the pain out of it. There is no durable consensus on what addiction is, what causes it, or what should be done about it. Meanwhile, it continues to increase around the world. This book argues that the cause of this failure to control addiction is that the conventional wisdom of the 19th and 20th centuries focused too single-mindedly on the afflicted individual addict. Although addiction obviously manifests itself in individual cases, its prevalence differs dramatically between societies. For example, it can be quite rare in a society for centuries, and then become common when a tribal culture is destroyed or a highly developed civilization collapses. When addiction becomes commonplace in a society, people become addicted not only to alcohol and drugs, but to a thousand other destructive pursuits: money, power, dysfunctional relationships, or video games. A social perspective on addiction does not deny individual differences in vulnerability to addiction, but it removes them from the foreground of attention, because social determinants are more powerful. This book shows that the social circumstances that spread addiction in a conquered tribe or a falling civilisation are also built into today's globalizing free-market society. A free-market society is magnificently productive, but it subjects people to irresistible pressures towards individualism and competition, tearing rich and poor alike from the close social and spiritual ties that normally constitute human life. People adapt to their dislocation by finding the best substitutes for a sustaining social and spiritual life that they can, and addiction serves this function all too well. The book argues that the most effective response to a growing addiction problem is a social and political one, rather than an individual one. Such a solution would not put the doctors, psychologists, social workers, policemen, and priests out of work, but it would incorporate their practices in a larger social project. The project is to reshape society with enough force and imagination to enable people to find social integration and meaning in everyday life. Then great numbers of them would not need to fill their inner void with addictions.
Psychology
Keywords: clinical psychology; disease & health Issues; psychiatry; psychology; psychopharmacology; public health; social science

Work After Globalization: Building Occupational Citizenship - Standing, Guy (Edward Elgar Publishing, 2010)
Per Google Books: This is a scholarly and erudite work. . . There is a wealth of detail, all illustrated with plenty of fascinating examples. . . It is impossible to give the full flavour of this thoughtful and stimulating book in even a long review, but it deserves to be
Sociology; Political Science
Keywords: business & economics - labor; business & economics - labour; embeddedness; industrial citizenship; political science / labor & industrial relations; political science / labour & industrial relations; social science / sociology / general

Karl Polanyi: the limits of the market - Dale, Gareth (Polity Press, 2010)
Karl Polanyi: The Limits of the Market is the first comprehensive introduction to Polanyi's ideas and legacy. It assesses not only the texts for which he is famous – prepared during his spells in American academia – but also his journalistic articles written in his first exile in Vienna, and lectures and pamphlets from his second exile, in Britain. It provides a detailed critical analysis of The Great Transformation, but also surveys Polanyi’s seminal writings in economic anthropology, the economic history of ancientand archaic societies, and political and economic theory. Its primary source base includes interviews with Polanyi's daughter, Kari Polanyi-Levitt, as well as the entire compass of his own published and unpublished writings in English and German. This engaging and accessible introduction to Polanyi's thinkingwill appeal to students and scholars across the social sciences,providing a refreshing perspective on the roots of our currenteconomic crisis.
Political Science
Keywords: economics; philosophy

Transformation als historischer Prozess: Karl Polanyi - Rebmann, Mara; Marmuth, Juliane (GRIN Verlag, 2010)
KM translate: Polanyi starts from the thesis that only the emergence of a liberal market economy with its "free play of the forces" led to that characteristic "separation" and self-sufficiency of the economy against society, which historically represents a novelty and bourgeois society of all others Distinguishes social information. With this thesis, the complex transformation of societies through the interaction with the economic order on the basis of Polanyi's work The Great Transformation will be descriptively explained and discussed. Here are his theses taken up and explained from his point of view.
Political Science
Keywords: Great Transformation; The (Book)